Forster resonant energy transfer in nanocrystal quantum dot structures - Lunz, Manuela (Trinity College (Dublin, Ireland). School of Physics, 2010)
Forster resonant energy transfer (FRET) is an energy transfer mechanism based on dipole-dipole interactions. FRET occurs in photosynthetic active organisms and is used in artificial structures to create energy flow in sensors, light-harvesting and light-emitting devices. It requires a spectral overlap of the energy donor and acceptor, the reason why semiconductor quantum dots (QDs) with their tunable, discrete energy level structure are ideal building blocks for FRET structures. Most FRET theories have been developed for donor and acceptor molecules, that are much smaller than QDs and don't show an inhomogeneous broadening. Although theoretical investigations have shown that these basic theories can also be used to describe FRET between QDs, only few comparisons of experiment and theory have been reported in literature. However, a detailed analysis and understanding of FRET between QDs are necessary to optimize the above mentioned FRET applications. Therefore, the objective of this thesis is to characterise FRET in different QD structures and to compare the observed trends with theoretical calculations. The layer-by-layer assembled structures discussed here, prepared with CdTe QDs of different sizes acting as energy donors and acceptors, are characterized by steady-state absorption and photoluminescence spectroscopy as well as by time-resolved photoluminescence measurements.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin